Mainstreaming Reproductive Mental Health of Women: The Unmet Need of the Hour - Chaitra , V (Indian Journal of Community Health, 2025)
Background: While the existing research is limited, over recent years, there has been growing awareness to understand the mental health of women during menstruation, menopause, and postpartum. Methodology: A woman's distinct reproductive life stages adversely affect her psychological well-being, aggravated by other underlying social, economic, and cultural factors. Drawing upon the analysis of governing laws and women’s reproductive health literature. Results: The existing reproductive health law, educational, and workplace frameworks in India are inadequate for supporting the reproductive mental health of women. Conclusion: It is of critical importance to adopt a holistic approach and call for mainstreaming the reproductive mental health of women through urgent legal and healthcare reforms.